2022
DOI: 10.1113/jp283427
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosylation of cardiac CaMKII at Cys290 mediates mechanical afterload‐induced increases in Ca2+ transient and Ca2+ sparks

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The CaMKIIδ-C290A knock-in mice were generated by the UC Davis Mouse Biology Core and have been described previously. 20 CaMKIIδ-C273S animals were generated using CRISPR/Cas9 genome editing at the Australian Phenomics Facility (Australian National University, Australia). For all mouse resources described here and materials listed below, please see the Major Resources Table in the Supplemental Material.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CaMKIIδ-C290A knock-in mice were generated by the UC Davis Mouse Biology Core and have been described previously. 20 CaMKIIδ-C273S animals were generated using CRISPR/Cas9 genome editing at the Australian Phenomics Facility (Australian National University, Australia). For all mouse resources described here and materials listed below, please see the Major Resources Table in the Supplemental Material.…”
Section: Methodsmentioning
confidence: 99%
“…19 S -nitrosylation at cysteine-290, following initial activation by Ca 2+ /CaM, causes autonomous activation of the kinase, consistent with the observation that NO exposure can enhance CaMKIIδ activity and increase Ca 2+ sparks. 11,13,20 In contrast, S -nitrosylation at cysteine-273 inhibits CaMKIIδ by preventing activation by Ca 2+ /CaM, 19 suggesting a dual role for NO in mediating CaMKIIδ activity that may be alternately protective or pathological depending on intracellular conditions.…”
mentioning
confidence: 99%
“… 42 Ca 2+ /calmodulin-dependent protein kinase II (CaMK II) is a serine/threonine protein kinase that can phosphorylate many proteins within cells, thereby increasing the intracellular calcium ion concentration. 43 After treating BMDMs with Yoda1 in calcium free medium, a decrease in the phosphorylation of Mob1 (a physiological substrate of Mst) was observed, indicating that eliminating extracellular Ca 2+ could inhibit the activation of Mst1/2 by Piezo1. These finding further confirmed that Ca 2+ was an important second messenger through which Piezo1 activates Mst1/2.…”
Section: Piezo1 Regulates Macrophage Involvement In the Inflammatory ...mentioning
confidence: 97%
“…Disulfide bridge formation (inter-subunit and inter-channel cross linking), glutathionylation by glutathione (GSH), nitrosylation by nitric oxide (NO) and phosphorylation by ROS-and RNSactivated CaMKII can all contribute to an increased RyR channel activity [71][72][73][74][75][76].…”
Section: Redox Modificationsmentioning
confidence: 99%